The growth performance and resistance to salinity stress of striped catfish Pangasius sp. juvenile in biofloc system with different feeding rates - Meritha, Wellya Wichi; Suprayudi, Muhammad Agus; Ekasari, Julie (Jurnal Akuakultur Indonesia, 2018)
ABSTRACTThis study aimed to evaluate the growth performance and resistance to salinity stress of striped catfish juvenile reared in biofloc with different feeding rate (FR). The treatments applied in this study were rearing the fish in biofloc with FR 5% and 8% of biomass per day, and rearing the fish with a FR of 8% per day without biofloc system as the control. The fish with an initial average length of 1.81 ± 0.20 cm were stocked in 9 units of  50 L aquaria with density of 40 ind/aquaria (800 ind/m3) for 15 days rearing period. In biofloc systems, the addition of tapioca as a source of organic carbon was done every day with an estimated C/N ratio of 10. No water exchange was done in biofloc systems, whereas regular water exchange was applied in the control. Results of the experiment showed that survival was not significantly different amongst treatments (P>0.05).  However, the specific growth rate of the fish in biofloc system with a FR of 8% per day showed the highest value and was significantly different from other treatments (P<0.05). Fish reared in biofloc system tend to have lower feed conversion ratios (FCRs) than the control. The lowest FCR was found in fish reared in biofloc system with 5% FR and significantly lower than control (P<0.05).  Salinity stress test was conducted by soaking 15 juveniles in water with a salinity of 20 g/L for an hour. The survival of fish after salinity stress test were significantly higher for fish reared in bifloc system than control (P<0.05). These data showed that rearing striped catfish juvenile in biofloc system could reduce FCR, increase the growth, and robustness of fish. Keywords: biofloc, feeding rate, growth, salinity stress test, striped catfish  ABSTRAKPenelitian ini bertujuan untuk mengevaluasi kinerja pertumbuhan dan ketahanan benih ikan patin terhadap stres salinitas yang dipelihara dalam sistem bioflok dengan tingkat pemberian pakan (FR) berbeda. Perlakuan yang terdapat dalam penelitian ini adalah benih patin yang dipelihara dalam sistem bioflok dengan FR 5% dan 8% per hari, dan pemeliharaan benih dengan FR 8% per hari tanpa penambahan sumber karbon sebagai kontrol. Benih patin dengan panjang rata-rata awal 1,81 ± 0,20 cm dipelihara dalam 9 unit akuarium dengan volume air 50 L dan kepadatan 40 ekor/akuarium (800 ekor/m3) selama 15 hari. Pada sistem bioflok, penambahan tapioka sebagai sumber karbon dilakukan setiap hari dengan C/N 10. Pada sistem bioflok tidak dilakukan pergantian air, sedangkan pada kontrol dilakukan pergantian air. Kelangsungan hidup ikan tidak berbeda nyata antar perlakuan. Namun, tingkat pertumbuhan spesifik ikan dalam sistem bioflok dengan FR 8% per hari menunjukkan nilai tertinggi dan berbeda nyata antar perlakuan (P<0,05). Benih yang dipelihara pada sistem bioflok memiliki rasio konversi pakan (FCR) yang lebih rendah dibandingkan kontrol, namun tidak terdapat perbedaan yang signifikan antara perlakuan bioflok (P>0,05). Uji stres salinitas dilakukan dengan merendam 15 ekor benih patin pada air dengan salinitas 20 g/L selama satu jam. Kelangsungan hidup setelah uji stres salinitas dari benih yang dipelihara di bioflok secara signifikan lebih tinggi dibandingkan kontrol (P<0,05). Hasil penelitian menunjukkan bahwa pemeliharaan benih patin pada sistem bioflok dapat menurunkan FCR, dan meningkatkan pertumbuhan dan ketahanan ikan terhadap stres salinitas. Kata kunci: bioflok, feeding rate, pertumbuhan, uji stres salinitas, ikan patin